Chemical vapor deposition of ferromagnetic chromium telluride nanowires - Ng, Jun Wen (Nanyang Technological University, 2024)
Since the discovery of Carbon Nanotubes (CNT), 1D materials have garnered significant attention due to their outstanding physical and chemical properties. Similarly, Transition Metal Dichalcogenides (TMDs) have also captured widespread interest for their ability to form structures with reduced dimensions, such as 2D nanoflakes and 1D nanowires, which exhibit intriguing properties. These materials find wide-ranging applications across various fields, including spintronics devices, memory storage, and catalysts in energy storage solutions. This report presents the pioneering synthesis of novel chromium telluride nanowires by adjusting the growth parameters like the H2 content, reacting temperature, and others. Further characterization confirms the successful synthesis of the nanowires, revealing a stoichiometry of Cr2Te3 and a trigonal crystal structure, along with ferromagnetic properties. These fascinating results not only open the door for 2D to 1D transition but also enhance the opportunities for investigating low-dimensional ferromagnetic properties.